PWE-197 Computed tomography derived lean muscle mass (LMM) does not predict cardiopulmonary exercise test (CPET) markers of physiological reserve. (22nd June 2015) - Jones, KI; Green, E; Franklin, J; Hurst, K; Atkinson, C; SIlva, MA
Abstract : Introduction: Lean muscle mass can be estimated by measuring psoas cross sectional area on computed tomography images, and is predictive of post-operative complications. Cardiopulmonary exercise testing (CPET) is a functional assessment of cardiopulmonary reserve providing individualised risk prediction. Given the independent predictive value of LMM and CPET, we hypothesised that LMM estimated using preoperative CT scans correlates with CPET and may be used as a surrogate marker for predicting complications following major hepatobiliary resection. Method: Patients undergoing major hepatobiliary resection with pre-operative CPET testing were included in the study. Clinicopathological and outcome data were collected retrospectively. Total Psoas Area (TPA) was measured at the level of the third lumbar vertebrae using the OsiriX software programme. Statistical data analyses were carried out using the Statistical Package for the Social Sciences (SPSS) version 20.0. Results: 30 patients were included in the study. The mean age was 72.8 years (+/-5.3) and 63% were male. 50% of the cohort were sarcopenic based on TPA measurements corrected for height and sex. Aerobic Threshold (AT), V02max and sarcopenia failed to predict post-operative (30 day) complications. There was no significant difference in AT or V02 max in sarcopenic versus non-sarcopenic patients (p = 0.73, p = 0.53). There was insignificant correlation between V02 max (r2=0.11 (95% C. I. 0.27–47) p = 0.3), AT (r2=0.32 (95% C. I. 0.07–0.63) p = 0.1) and TPA/H 2 . Conclusion: This novel investigation does not support the use of radiologically estimated lean muscle mass as a surrogate marker of CPET assessed physiological reserve in patients undergoing hepatobiliary resection. The prevalence of sarcopenia is significant (50%) in this population, which limits the sensitivity of sarcopenia in predicting complications. Disclosure of interest: None Declared.